2014
DOI: 10.2134/jeq2013.10.0415
|View full text |Cite
|
Sign up to set email alerts
|

Dry Mature Fine Tailings as Oil Sands Reclamation Substrates for Three Native Grasses

Abstract: Mature fine tailings (MFT) are a by-product of oil sands mining that must be reclaimed through capping or use as a reclamation substrate. Some chemical and physical properties of MFT make it inhospitable for plant growth, such as high concentrations of sodium, sulfate, chloride, and hydrocarbons. A greenhouse study assessed whether substrates of various mixes of dry MFT, overburden sand, and peat mineral soil mix (PMM) and caps of forest floor organic material (LFH) and PMM would support the emergence and grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
6
18
0
Order By: Relevance
“…According to the optimality theory (Espeleta and Donovan 2002), trees growing in a nutrient and water-limited environment would be expected to maximize their nutrient uptake by increasing their fine root productivity and turnover rate. This has been demonstrated in previous studies that focused on water and nutrient limitations in reclaimed sites with tailings sand as a substrate (Naeth et al 2011;Jung et al 2014;Luna Wolter and Naeth 2014). Fine root growth is typically influenced by available nutrients in forest ecosystems (Ingestad and Agren 1991) and given the significant response for fine root biomass and turnover rate across the productivity gradient that is likely the case in our study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…According to the optimality theory (Espeleta and Donovan 2002), trees growing in a nutrient and water-limited environment would be expected to maximize their nutrient uptake by increasing their fine root productivity and turnover rate. This has been demonstrated in previous studies that focused on water and nutrient limitations in reclaimed sites with tailings sand as a substrate (Naeth et al 2011;Jung et al 2014;Luna Wolter and Naeth 2014). Fine root growth is typically influenced by available nutrients in forest ecosystems (Ingestad and Agren 1991) and given the significant response for fine root biomass and turnover rate across the productivity gradient that is likely the case in our study.…”
Section: Discussionsupporting
confidence: 76%
“…; Jung et al. ; Luna Wolter and Naeth ). Fine root growth is typically influenced by available nutrients in forest ecosystems (Ingestad and Agren ) and given the significant response for fine root biomass and turnover rate across the productivity gradient that is likely the case in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Plants do not grow well directly in oil sands tailings (Renault et al 2004;Luna Wolter and Naeth 2014). Boldt-Burisch et al (2018) grew slender wheatgrass (Elymus trachycaulus) and bird's-foot trefoil (Lotus corniculatus) in dry MFT, coarse tailings sand (CTS), and in sandy soil, and found that both species had reduced growth in both the MFT and CTS compared with the sandy soil.…”
Section: Introductionmentioning
confidence: 99%
“…Renault et al (2000) also found that seedling survival in conifers was reduced to as low as 55% when grown directly in dry MFT. For this reason, adding a capping material plays an important role in reclamation by improving plant growth (Hargreaves et al 2012;Luna Wolter and Naeth 2014;Huang et al 2015), increasing water storage (Zettl et al 2011), and improving soil conditions to support self-sustaining ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation